2010
DOI: 10.1167/iovs.09-4438
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Regulation of NMDA Receptor Subunit Composition and Phosphorylation in the Retina and Visual Cortex

Abstract: Purpose. Experimental manipulation of experience during development can have profound effects on the functioning of the resulting circuits. N-methyl-d-aspartate glutamate receptor (NMDAR) activity is required for the establishment and refinement of neural circuits during development. In the present study, the authors addressed the issue of experience-dependent regulation of NMDARs by examining the effects of visual experience and deprivation on subunit composition and subunit phosphorylation of NMDAR in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…We and others have previously shown that dark rearing decreases NR2A and increases NR2B phosphorylation at serine 1303, with no change in NR2B protein levels in rat retina [42,43]. Therefore, taken together with the present results, it appears that visual experience can affect alternative splicing of the NR1 subunit in the retina in addition to NMDAR subunit composition and phosphorylation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We and others have previously shown that dark rearing decreases NR2A and increases NR2B phosphorylation at serine 1303, with no change in NR2B protein levels in rat retina [42,43]. Therefore, taken together with the present results, it appears that visual experience can affect alternative splicing of the NR1 subunit in the retina in addition to NMDAR subunit composition and phosphorylation.…”
Section: Discussionsupporting
confidence: 80%
“…During retinal development, shortening of the NMDAR-mediated currents is observed in rat RGCs and this event is prevented by dark rearing the animals for 1 month [41]. Furthermore, modifications of retinal NMDAR subunit expression are observed during development and by dark rearing [28,[41][42][43]. In addition, visual experience regulates the development of retinal circuitry itself.…”
Section: Introductionmentioning
confidence: 99%
“…However, measured biochemically, the level of diversity is less clear. Activation of CamKII ( Lisman et al, 2012 ), mobilization of SynGAP ( Araki et al, 2015 , 2020 ; Lautz et al, 2018 ) phosphorylation of NMDA receptors (NMDARs) ( Giannakopoulos et al, 2010 ; Rosenblum et al, 1996 ; Trepanier et al, 2012 ), and release of mGluR5 from Homer scaffolds ( Guo et al, 2015 ; Lautz et al, 2018 ; Ronesi et al, 2012 ) have been described for hippocampal or neocortical neurons, and likely occur elsewhere. However, the molecular rules that control plasticity may differ across brain areas; for example, at hippocampal synapses, kinase activation mediates long-term potentiation (LTP), whereas cerebellar LTP is mediated by phosphatase activation ( Belmeguenai and Hansel, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, measured biochemically, the level of diversity is less clear. Activation of CamKII [26], mobilization of SynGAP [27][28][29] phosphorylation of NMDARs [30][31][32], and release of mGluR5 from Homer scaffolds [29,33,34] have been described for hippocampal or neocortical neurons, and likely occur elsewhere. At a proteomic level, induction of long-term potentiation (LTP) in the hippocampus has been shown to alter the phosphorylation status of 570 sites across 220 postsynaptic proteins [35].…”
Section: Introductionmentioning
confidence: 99%